Assessing Transportation Patterns in the Azores Archipelago - Rui Alexandre Castanho; José Manuel Naranjo Gómez; Ana Vulevic; Arian Behradfar; Gualter Couto (Infrastructures, 2021)
It is well-known that the ultra-peripheral territories as Islands present several limitations such as the lack of resources, restricted land, mass tourism, and barriers to movement, and connectivity between urban centers. These obstacles make ultra-peripheral regions suitable case studies considering their territorial governance and consequently, sustainable development and growth. Thus, transportation and infrastructure sustainability in these regions are not an exception. Considering all the obstacles present in these regions, the accessibility and connectivity patterns that the local population has in these territories should be assessed and monitored. Thereby, through exploratory tools, the present research assumes to examine, using accessibility and connectivity indicators, the consequences across the social-economic dimension that the regional transportation and infrastructure should convey to the Azores Islands Archipelago populations. Therefore, this article allows us to set the present situation regarding this region’s accessibility and connectivity patterns, creating an additional tool for supporting the main actors’ design and implementation of these territories’ future plans and strategies. Besides, this study enables us to recognize that Pico, Flores, and São Miguel are the ones with better accessibility patterns within the Azores Archipelago.